2014
DOI: 10.1242/dev.104067
|View full text |Cite
|
Sign up to set email alerts
|

The development of zebrafish tendon and ligament progenitors

Abstract: Despite the importance of tendons and ligaments for transmitting movement and providing stability to the musculoskeletal system, their development is considerably less well understood than that of the tissues they serve to connect. Zebrafish have been widely used to address questions in muscle and skeletal development, yet few studies describe their tendon and ligament tissues. We have analyzed in zebrafish the expression of several genes known to be enriched in mammalian tendons and ligaments, including scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(182 citation statements)
references
References 77 publications
4
178
0
Order By: Relevance
“…Skeletogenic cells surrounding the notochord have been shown to originate from the sclerotome compartment ventral to the myotome (Morin-Kensicki and Eisen, 1997). Although awaiting definitive evidence, it is likely that myoseptal/tendon cells originate from a sclerotome derivedcompartment similar to the syndetome of the amniotes (Bricard et al, 2014;Chen and Galloway, 2014;Subramanian and Schilling, 2014). Thus, although myoseptal and skeletogenic cells are likely to share a common sclerotomal origin, they rapidly differ not only by the expression of scleraxis and Osf2/periostin as previously reported (Bricard et al, 2014) but also by that of CILP1.…”
Section: Ralliere Et Almentioning
confidence: 55%
See 3 more Smart Citations
“…Skeletogenic cells surrounding the notochord have been shown to originate from the sclerotome compartment ventral to the myotome (Morin-Kensicki and Eisen, 1997). Although awaiting definitive evidence, it is likely that myoseptal/tendon cells originate from a sclerotome derivedcompartment similar to the syndetome of the amniotes (Bricard et al, 2014;Chen and Galloway, 2014;Subramanian and Schilling, 2014). Thus, although myoseptal and skeletogenic cells are likely to share a common sclerotomal origin, they rapidly differ not only by the expression of scleraxis and Osf2/periostin as previously reported (Bricard et al, 2014) but also by that of CILP1.…”
Section: Ralliere Et Almentioning
confidence: 55%
“…CILP1 expression was found to concentrate in myoseptal/tendon cells invading medio-laterally into the space separating adjacent myotomes (Fig.4 D and E). Myoseptal cells have been shown to express scleraxis, tenomodulin and tendon associated collagens and, as such, may be considered homologous to axial tenocytes in amniotes (Bricard et al, 2014;Chen and Galloway, 2014). Using combined fluorescence localization of CILP1 mRNA and osteoblastspecific factor 2 (Osf2)/periostin mRNA, we further observed that CILP1 labelling was excluded from the Osf2/periostin-expressing skeletogenic cells that surround the notochord and are abutted by the most medial CILP1 positive myoseptal cells (Fig.…”
Section: Fig 3 (Above Right) Embryonic Expression Of Cilp1 In the Tmentioning
confidence: 86%
See 2 more Smart Citations
“…In the developing embryo, the induction of axial tendons in the tenogenic compartment, the syndetome, was shown to depend on signals emanating from the adjacent myotome, as disruption of myotome formation in chick and mouse embryos resulted in failure of tendon progenitor induction (Brent et al, 2005;Brent and Tabin, 2004;Chen and Galloway, 2014). By contrast, induction of cranial tendon progenitors was not disrupted in the absence of muscle, but subsequent differentiation of cranial tendons failed in 'muscle-less' mutants (Chen and Galloway, 2014;Grenier et al, 2009;Grifone et al, 2008).…”
Section: Introductionmentioning
confidence: 99%